Cerebral malaria: mechanisms of brain injury and strategies for improved neurocognitive outcome. - Idro, R; Marsh, K; John, C; Newton, C (2010)
Cerebral malaria is the most severe neurological complication of infection with Plasmodium falciparum. With >575,000 cases annually, children in sub-Saharan Africa are the most affected. Surviving patients have an increased risk of neurological and cognitive deficits, behavioral difficulties, and epilepsy making cerebral malaria a leading cause of childhood neurodisability in the region. The pathogenesis of neurocognitive sequelae is poorly understood: coma develops through multiple mechanisms and there may be several mechanisms of brain injury. It is unclear how an intravascular parasite causes such brain injury. Understanding these mechanisms is important to develop appropriate neuroprotective interventions. This article examines possible mechanisms of brain injury in cerebral malaria, relating this to the pathogenesis of the disease, and explores prospects for improved neurocognitive outcome.